(untitled) (International Journal of Advanced Research in Computer Science, 2017)
The Software testing is done to ensure the quality characteristics of an application like functionality, performance, usability, scalability. Performance testing is a technique for quality assurance. It is a way of testing web applications to guarantee that the applications will perform properly under their expected normal workload. Features and Functionalities supported by a software system is not the sole concern. A software application’s performance like its response time, do make a difference. The objective of performance testing is not to discover bugs but to eliminate performance bottlenecks. Performance testing is mainly categorised as Stress and Load testing. JMeter is an Open Source tool, widely used to measure performance parameters of an application. It is a java application for load testing and measuring performance. This paper presents performance testing concepts and a comparative analysis of web applications in terms of its response time, throughput and deviation, proposing a way to increase revenue for web application Industry. Keywords: software testing; web testing; performance testing; Jmeter; load testing; response time